Household expectations and dissent among policymakers - Moritz Grebe; Peter Tillmann (Philipps-University Marburg, School of Business and Economics, 2022)
This paper studies the impact of dissent in the ECB's Governing Council on uncertainty surrounding households' inflation expectations. We conduct a randomized controlled trial using the Bundesbank Online Panel Households. Participants are provided with alternative information treatments concerning the vote in the Council, e.g. unanimity and dissent, and are asked to submit probabilistic in ation expectations. The results show that the vote is informative. Households revise their subjective in ation forecast after receiving information about the vote. Dissenting votes cause a wider individual distribution of future in ation. Hence, dissent increases households' uncertainty about inflation. This effect is statistically significant once we allow for the interaction between the treatments and individual characteristics of respondents. The results are robust with respect to alternative measures of forecast uncertainty and hold for different model specifications. Our findings suggest that providing information about dissenting votes without additional information about the nature of dissent is detrimental to coordinating household expectations.
Keywords: E52; E43; E32; 330; central bank communication; disagreement; ination expectations; randomized controlled trial; survey